EFFECT OF TRUWINIST INTERDIGITAL METHOD IN KNOWLEDGE AND SKILL OF SELECTING DRUG AND WRITING PRESCRIPTION OF ASTHMA DRUG - Truly Deti Rose Sitorus; Eggy Raynaldi Rachman Nurhadi; Novi Vicahyani Utami; Muhammad Hasan Bashari (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: Medical error is any kind of unplanned or out of procedure medical action. Some of them are error in selecting and prescribing drug which might cause the disease to remain, worse, or death. Prescribing error can be prevented by giving better education about pharmacology. One popular learning methods is blended learning. Truwinist Interdigital Method is a learning media innovation with bleanded learning concept designed subjects in audiovisual form. Truwinist Interdigital Method was accessible at university’s learning management system. This study aimed to evaluate the improvement of student’s pharmacological learning outcome upon Truwinist Interdigital Method. The learning outcome was students knowledge and skill on prescribing asthmatic drug. Methods: A experimental research was conducted with pretest and posttest design. Subjects were 148 medical students of Universitas Padjadjaran who were given Truwinist Interdigital Method. The learning outcome was observed using pre-test and post-test score and tested using Wilcolson test. Results: Students’ knowledge score increased from average of 34.70±15.43 to 86.01±10.80. Students’ skill score increased from average of 25.31±12.76 to 76.93±10.66. The result showed students’ learning outcome increased significantly (p<0,001). Conclusion: Knowledge and prescribing skill Students’ asthmatic drug increase after using bleanded learning with Truwinist Interdigital Method.